EFEKTIVITAS METODE SIMULASI DALAM MENINGKATKAN PEMAHAMAN KONSEP DAN KETERAMPILAN BERPIKIR KRITIS SISWA PENDIDIKAN DASAR DI ERA DIGITAL - Nadhifa Aufah Chafshah; Icha Mufassiroh Asy-Syauqi; Imam Syafe’i; Eti Hadiati; Ratu Vina Rahmatika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of simulation methods in improving students' conceptual understanding and critical thinking skills in elementary education within the digital era. Using a quasi-experimental approach with a pretest-posttest control group design, the study involved students from an elementary school. Data were collected through observation, tests, and interviews. The results indicate that students taught with simulation methods demonstrated significantly higher improvement in conceptual understanding and critical thinking compared to those taught with conventional methods. This research highlights the potential of digital-based simulations as an innovative pedagogical tool in elementary education.